Employment analysis of North Kalimantan Province 2018-2020 - Kusumawardhani, Ekky Elfira; Ruth Boru Girsang, Michelle; Nurjanah, Siti; Fiore, Katyusha; Pitoyo, Jendra Satria; Putri, Ratih Fitria (EDP Sciences, 2023)
Employment is one of the important factors in national development. This study aims to analyze the employment conditions of North Kalimantan Province, from the workforce to the unemployment rate. The average LFPR (Labour Force Participation Rate) in North Kalimantan Province in 2020 is 66.51. Especially in the district which has many coal and mineral industries, the initial LFPR was 75.04 in Malinau Regency. Kalimantan Province's EPR based on age group shows that in 2018, 2019, and 2020 there are not too many differences in EPR (Employment to Population Ratio) levels. The lowest EPR is always in the 15-19 age group with an EPR of 22.94; 17.95; and 24.73. Tarakan City has a higher TPT (Open Unemployment Rate) value than other districts, even compared to North Kalimantan Province with 5.89, 5.3, 5.86, and 4.14. North Kalimantan experienced a decrease in the underemployment rate of 0.37 in 2018—2019. Then in 2020, all districts/cities in North Kalimantan experienced an increase in the underemployment rate. © 2023 EDP Sciences. All rights reserved.